2015
DOI: 10.1007/s00430-015-0420-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycobacterium avium subsp. paratuberculosis and Escherichia coli in blood samples from patients with inflammatory bowel disease

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) and adherent-invasive Escherichia coli (AIEC) have been implicated as primary triggers in Crohn's disease (CD). In this study, we evaluated the prevalence of MAP and E. coli (EC) DNA in peripheral blood from 202 inflammatory bowel disease (IBD) patients at various disease periods and compared against 24 cirrhotic patients with ascites (CIR) (non-IBD controls) and 29 healthy controls (HC). MAP DNA was detected by IS900-specific nested PCR, EC DNA by malB-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 70 publications
(86 reference statements)
0
30
0
Order By: Relevance
“…In IBDs, there is a significant reduction in beneficial bacteria, including Firmicutes, Bacteroidetes, Actinobacteria, and Verrucomicrobia, with a concomitant increase in anaerobic bacteria of the family Enterobacteriaceae, playing a pathogenic role in the inflamed colon (Zuo & Ng, ). Despite there still being no identification of causative microorganism in IBDs, multiple studies suggested the involvement of pathogens such as Mycobacterium avium paratuberculosis , Clostridium difficile , and Helicobacter and altered commensals such as adherent‐invasive E. coli (Issa et al, ; Thomson et al, ; Nazareth et al, ; Palmela et al, ), whereas case report studies indicated the inflamed colon as a favorable environment for infection of different opportunistic pathogens, including P. aeruginosa and S. aureus (Bettenworth et al, ; Iguidbashian et al, ). A great deal of interest also emerged as regards the involvement of fungi in colon inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In IBDs, there is a significant reduction in beneficial bacteria, including Firmicutes, Bacteroidetes, Actinobacteria, and Verrucomicrobia, with a concomitant increase in anaerobic bacteria of the family Enterobacteriaceae, playing a pathogenic role in the inflamed colon (Zuo & Ng, ). Despite there still being no identification of causative microorganism in IBDs, multiple studies suggested the involvement of pathogens such as Mycobacterium avium paratuberculosis , Clostridium difficile , and Helicobacter and altered commensals such as adherent‐invasive E. coli (Issa et al, ; Thomson et al, ; Nazareth et al, ; Palmela et al, ), whereas case report studies indicated the inflamed colon as a favorable environment for infection of different opportunistic pathogens, including P. aeruginosa and S. aureus (Bettenworth et al, ; Iguidbashian et al, ). A great deal of interest also emerged as regards the involvement of fungi in colon inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, considering the potential of P. fruticosa as a source of antimicrobial agents (Ristic et al, 2000), we performed a parallel set of experiments in order to evaluate the effects of P. fruticosa and P. herba-venti on Gram-positive and Gram-negative bacterial strains and fungal species involved in IBDs (Guo et al, 2015;Iguidbashian et al, 2018;Trojanowska et al, 2010;Wang et al, 2018). Microbiome dysbiosis is an increase in the number of bacteria associated with colon mucosa, alongside a reduction in biodiversity (Kaur, Chen, Luther, & Kao, 2011 Helicobacter and altered commensals such as adherent-invasive E. coli (Issa et al, 2007;Thomson et al, 2011;Nazareth et al, 2015;Palmela et al, 2018), whereas case report studies indicated the inflamed colon as a favorable environment for infection of different opportunistic pathogens, including P. aeruginosa and S. aureus (Bettenworth et al, 2013;Iguidbashian et al, 2018). A great deal of interest also emerged as regards the involvement of fungi in colon…”
Section: Toxicological and Pharmacological Profilementioning
confidence: 99%
“…In one study, peripheral blood from patients with active Crohn's disease had MAP DNA prevalence of 68%, while those with Crohn's in any stage had E. coli 80% of the time. 52 In subjects whose sera tested positive for antigens against MAP, early uncontrolled trials suggested antibiotics against MAP could induce symptomatic improvement. [53][54][55] A large randomized controlled in trial from Australia found an early clinical benefit of antibiotics for MAP in addition to steroids compared to placebo (week 16, 66% v. 50%, p D 0.02).…”
Section: Specific Bacteria Are Associated With Ibdmentioning
confidence: 99%
“…Greenstein et al (2007) showed that the accepted use of methotrexate and 6-mercaptopurine (6-MP) for therapy of IBD may be due to the inhibitory action of the drugs on MAP, instead of the generally prevailing idea that the primary mechanism of action is the drug's ability to decrease the production of pro-inflammatory cytokines. Nazareth et al (2015) investigated the growth of MAP in macrophages of CD patients under the influences of Infliximab treatment. A lower MAP CFU count was reported in macrophage cultures.…”
Section: Antimicrobial Options For Map With Special Reference To Nanomentioning
confidence: 99%